Drinking Non-nutritive Sweetness Solution of Sodium Saccharin or Rebaudioside a for Guinea Pigs: Influence on Histologic Change and Expression of Sweet Taste Receptors in Testis and Epididymis - Shen, Ting; Li, Junrong (Frontiers in Nutrition, 2021)
Thirty 4-week-old male guinea pigs with body weight 245.73 ± 6.02 g were randomly divided into five groups (n=6), received normal water (control group), equivalent sweetness low dose or high dose of sodium saccharin (L-SS, 1.5 mM or H-SS, 7.5 mM) or rebaudioside A (L-RA, 0.5 mM or H-RA, 2.5 mM) solution for 28 consecutive days. The results showed that the testicular and epididymal weight in male guinea pig with age of 56 d represented no significant difference among all groups, in spite of heavier body weight in L-SS and H-RA, NNS contributes no significant influence on serum testosterone and estradiol level. Low-dose 0.5 mM rebaudioside A enhanced testicular and epididymal functions by elevating the expression of T1R2 and GNAT3, high-dose 7.5 mM sodium saccharin exerted adverse morphologic influences on testis and epididymis with no effect on expression of T1R2, T1R3 and GNAT3. In conclusion, dose-response biological manners to the equivalent sweetness NNS with artificial and natural sweeteners requires further study in prolonged exposure, which will provide evidences to understand the biological impact of this widespread NNS consumption.